Rituximab versus splenectomy in persistent or chronic adult primary immune thrombocytopenia: an adjusted comparison of mortality and morbidity. Issue 1 (30th September 2013) - Moulis, Guillaume; Sailler, Laurent; Sommet, Agnès; Lapeyre‐Mestre, Maryse; Derumeaux, Hélène; Adoue, Daniel
<x xml:space="preserve">Abstract</x> Splenectomy and rituximab are both recommended as second‐line treatment in immune thrombocytopenia (ITP), but they have never been directly compared. We compared their efficacy and serious adverse outcomes in a retrospective cohort of 105 adult primary ITP patients exposed to one or other of these treatments. Primary outcome was composite: death from hemorrhage or from infection and hospitalization for bleeding or for infection. Secondary outcomes were overall mortality, hospitalization for bleeding, hospitalization for infection, as well as response and complete response (international definitions). Analyses were adjusted on a propensity score. Patients treated with rituximab (n = 43) were older and had more comorbidities than the splenectomized patients (n = 62). Mean follow‐up was, respectively, 3 and 8.4 years. After adjustment on the propensity score, there was no difference between the two groups regarding the primary and other clinical outcomes. In the multivariate analysis, only a history of mucosal bleeding (HR 3.2 95% CI [1.2–8.5]) and a Charlson score ≥1 (HR 4.2 95% CI [1.8–9.6]) were associated with the primary outcome. These two factors were also associated with hospitalization for bleeding. As expected, response, complete response and maintenance rates were higher in the splenectomy group. Splenectomy compared with rituximab was independently associated with a response at 12 months (OR 4.4, 95% CI [1.7–11.8]). Then, adjusted analyses in this real‐life cohort confirmed the better results of splenectomy compared with rituximab. Am. J. Hematol. 89:41–46, 2014. © 2013 Wiley Periodicals, Inc.